The Mediating Role of Leisure Satisfaction between Work and Family Domain and Work-Life Balance - Kong, Edwina Yan Ying; Zaiton, Hassan; Nur Fatihah, Abdullah Bandar (UNIMAS Publisher, 2020)
This study aimed to determine the mediating role of leisure satisfaction between work domain (work overload and job involvement), family domain (family workload and family support) and work-life balance among teachers in Kuching. Fifty employees responded to the self-administered questionnaire in one of a primary school in Kuching area. Data was analyzed Pearson Correlation, Regression and Sobel Test. Results indicated that work overload and family workload are negative and significantly influence employee work-life balance while job involvement and family support are positive and significantly effect work-life balance. This research revealed work overload, job involvement, family workload, family support, and work-life balance are partially mediated by leisure satisfaction. Thus, it is recommended for organizations to organize variety of leisure activities as a strategy to assist employees to improve work-life balance.